Discovery of amino acid substitutions in penicillin-binding proteins associated with adaptation to D-Ala-D-Lac in vancomycin-resistant Enterococcus faecalis - Nese Caglayan; Banu Sancak; Zeynep Kanlidere; Tanil Kocagoz; Tanil Kocagoz (Frontiers in Cellular and Infection Microbiology)
The bacterial cell wall, essential for structural integrity, is synthesized with penicillin-binding proteins (PBPs). Vancomycin-resistant enterococci (VRE) evades vancomycin by replacing D-Ala-D-Ala in their cell wall precursors with D-Ala-D-Lac, reducing the drug’s effectiveness. However, how PBPs-which typically use D-Ala-D-Ala as a substrate-adapt to recognize D-Ala-D-Lac remains unclear. Here, we performed Sanger sequencing and alignment of PBP genes from both vancomycin-susceptible and -resistant E. faecalis strains to identify mutations, following amplification by PCR. We then applied homology modeling to assess structural impacts of these changes on PBPs and conducted docking studies to investigate ligand-binding interactions. For the first time, we identified specific adaptations in certain VRE PBPs that may facilitate the D-Ala-D-Lac utilization. We found that PBP1B, PBP2A, PBP3 showed changes, while PBP1A, PBP2B and PBP4 remained unchanged. Notably, a threonine-to-asparagine substitution at location 491 in PBP1B leads to a shift in substrate preference from D-Ala-D-Ala to D-Ala-D-Lac. Similar structural changes in PBP3 suggest that the presence of changed and unchanged PBPs within the same classes suggests compensatory interactions, indicating a teamwork among multiple PBPs. These insights into PBPs provide a deeper understanding of D-Ala-D-Lac utilization in VRE, may be used to develop new therapeutic agents to combat vancomycin resistance.